Investigasi Niat Belanja Ulang Ke Toko Pakaian: Peran CRM, Kepuasan Dan Loyalitas Pelanggan - Aidha Savitri; Usep Suhud (Universitas Serang Raya, 2018)
In this era of globalization the fashion industry in Indonesia is growing rapidly because public awareness for personal appearance is increasing. From many fashion brands, companies must have a strategy to stay afloat in business. Companies from various fashion industries must stay in touch with customers, through CRM or Customer Relationship Management in order to increase customer satisfaction that will make loyal customers that can affect repurchase intention. This study was conducted to find information from Customer Relationship Management to customer satisfaction and customer loyalty and how it impacts repurchase intention in a clothing store. This research was conducted by spreading questionnaires to 200 respondents using nonprobability sampling, convenience sampling. This research uses Exploratory Factor Analysis to test its validity and cronbach alpha to test the reliability. This research also uses a Structural Equation Model to test the hypothesis by using AMOS. From 5 hypotheses, in this research, 4 hypotheses have a positive and significant influence.Keywords: customer relationship management, customer satisfaction, customer loyalty, repurchase intention.